2006
DOI: 10.2503/jjshs.75.1
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Dwarfing Pear Rootstock Clones from Pyrus betulaefolia and P. calleryana Seedlings

Abstract: A rootstock trial has been established to develop dwarfing pear rootstock clones from Pyrus species. Seedlings that were raised from the open-pollinated seeds of P. betulaefolia Bunge (PB) and P. calleryana Decne (PC); and showed significant genetic dwarfing growth and good traits based on ease of clonal propagation were screened. Among those, four seedlings of PB named SPRB1, SPRB13, SPRB15, and SPRB22 (SPRB = Shinshu University Pear Rootstock P. betulaefolia clone) and six seedlings of PC named SPRC3, SPRC5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Ten genetically dwarfing Pyrus rootstock clones derived from open-pollinated progenies of PB and PC were selected after an 8-year of experimental field test, were evaluated with different anaerobic root environments. Dwarfing clones were generated from the inherently dwarfish seedlings with excellent rooting ability by asexual propagation (Robbani et al, 2006). The selected clones from PB and PC were named SPRB (Shinshu University Pear Rootstock P. betulaefolia clone) and SPRC (Shinshu University Pear Rootstock P. calleryana clone), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Ten genetically dwarfing Pyrus rootstock clones derived from open-pollinated progenies of PB and PC were selected after an 8-year of experimental field test, were evaluated with different anaerobic root environments. Dwarfing clones were generated from the inherently dwarfish seedlings with excellent rooting ability by asexual propagation (Robbani et al, 2006). The selected clones from PB and PC were named SPRB (Shinshu University Pear Rootstock P. betulaefolia clone) and SPRC (Shinshu University Pear Rootstock P. calleryana clone), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…As a variety of Oriental pear (Asian pear) [36], it is native to East Asia and mainly distributed in China, Korean peninsula and Japan [37]. It has good grafting affinity with the Oriental pear and Western pear, and is an important parent of dwarf rootstock and resistance breeding [38,39]. It is the main grafting stock of pear varieties in northern China.…”
Section: Introductionmentioning
confidence: 99%
“…3). Robbani et al (2006b) demonstrated that rootstock species capable of surviving long periods of flood conditions developed adventitious roots at the water line. Tamura et al (1996b) found that flooding caused an increase in above-ground 1-aminocyclopropane-1-carboxylic acid (ACC) content and ethylene production in pear rootstocks seedlings; it is, thus, believed that production of ethylene as a result flood stress induces the development of adventitious roots as reported in the other higher plants (Bradford and Dilley, 1978;Bradford and Yang, 1980;Kawase, 1976;Rowe and Beardsell, 1973).…”
Section: ) Research On Drought Tolerancementioning
confidence: 99%